Different Characteristics of the Corticospinal Tract According to the Cerebral Origin: DTI Study - Seo, J.P.; Jang, S.H. (American journal of neuroradiology : AJNR, 2013)
Little is known about differences in corticospinal tract fibers according to cerebral origin. Using diffusion tensor tractography, we attempted to investigate the characteristics of the CST according to the cerebral origin in the human brain. Thirty-six healthy subjects were recruited for this study. A 1.5T Gyroscan Intera system was used for acquisition of DTI. CSTs were reconstructed by selection of fibers passing through seed and target ROIs: seed ROIs, the area of the CST at the pontomedullary junction; target ROIs, the primary motor cortex, the primary somatosensory cortex, the dorsal premotor cortex, and the supplementary motor area. A significant difference in tract volume was observed in each ROI (P < .05): M1 (2373.6, 36.9%), S1 (2037.7, 31.7%), SMA (1588.0, 24.7%), and dPMC (429.8, 6.7%). Regarding fractional anisotropy values, the dPMC or SMA showed higher values than the M1 or S1; however, the opposite occurred in terms of the mean diffusivity value (P < .05). In addition, fractional anisotropy and mean diffusivity values of the dPMC differed from those of the SMA (P < .05); in contrast, no significant difference was observed between the M1 and S1 (P > .05). Tract volume was found to differ according to cerebral origin and was, in descending order, M1, S1, SMA, and dPMC. In addition, the directionality and diffusivity of CST fibers in the SMA and the dPMC differed from those of the M1 and S1, which showed similar characteristics.